Energy system involvement in female rowers during a 2000m race simulation - Martin, D.; Roberts, A. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
The purpose of this study was to analyse the energy cost of racing 2000m in female rowers. Four national level heavyweight female rowers, mean age 19.3 years (range 19-20 years) completed a maximal 2000m race simulation on a Concept II rowing ergometer to determine the relative contributions of aerobic and anaerobic energy sources. Oxygen uptake (VO2), heart rate (HR), and post-test blood lactate measurements were recorded. Total energy cost was estimated by extrapolation of the regression equation VO2= 0.114 speed (m·sec-1)2.42 and the Accumulated Oxygen Deficit (AOD) method was used to calculate the contribution of the anaerobic energy system. Mean ± SD VO2peak achieved in the race was 4.21 ± 0.36 L·min-1 and the mean AOD was 3.74 ± 2.05 L. Mean maximal HR was 197 ± 9 bmp and mean post-test lactate was 13.7 ± 1.8 mM. The mean time taken for the rowers to complete the test was 7:21 min:sec. The aerobic system represented 88.6% of the estimated total energy cost, while the anaerobic system accounted for the remaining 11.4%. Rowers utilised 62% of their AOD during the first 2 minutes of the race simulation and maintained a mean race intensity of 98% of VO2peak. This study has demonstrated that racing 2000m is predominantly an aerobic activity, but does require a large anaerobic contribution. Both high aerobic power and anaerobic capacity are necessary components to success in heavyweight women`s rowing. This suggests a need to develop and implement training programmes that enhance both these physical attributes.